2018
DOI: 10.3390/en11040915
|View full text |Cite
|
Sign up to set email alerts
|

Passive Fuel Cell Heat Recovery Using Heat Pipes to Enhance Metal Hydride Canisters Hydrogen Discharge Rate: An Experimental Simulation

Abstract: This paper reports on an experimental investigation of a passive thermal coupling arrangement between a Proton Exchange Membrane (PEM) fuel cell and a Metal Hydride (MH) hydrogen storage canister using heat pipes for enhancing the release rate of hydrogen. The performance of this arrangement was measured by inserting the evaporator sections of the heat pipes into an aluminum plate mimicking one out of five cooling plates of a 500-W fuel cell (that is a 100 W section of the stack). Thermal pads were attached on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…The results showed that the application of a heat pipe can keep the temperature of the PEMFC within the ideal range and achieve a better temperature uniformity. Tetuko et al established a passive thermal bridge between the PEMFC and metal hydrogen canisters using passive cooling and a circular heat pipe of high thermal conductivity. They flattened the evaporation section and got it integrated into the PEMFC.…”
Section: Micro Heat Pipe Coupled Proton Exchange Membrane Fuel Cellmentioning
confidence: 99%
“…The results showed that the application of a heat pipe can keep the temperature of the PEMFC within the ideal range and achieve a better temperature uniformity. Tetuko et al established a passive thermal bridge between the PEMFC and metal hydrogen canisters using passive cooling and a circular heat pipe of high thermal conductivity. They flattened the evaporation section and got it integrated into the PEMFC.…”
Section: Micro Heat Pipe Coupled Proton Exchange Membrane Fuel Cellmentioning
confidence: 99%
“…The excess hydrogen available can be part of the solution to lift this barrier and encourage the utilisation of hydrogen fuel cell vehicles. It is important to consider this point that hydrogen fuel cell systems generate heat, as well as electricity [67,68]. Part of the total heat generated by the fuel cell that is available for recovery (i.e., Q in W) can be calculated from the following equation [69]:…”
Section: Alternative Scenariosmentioning
confidence: 99%
“…Figure 1 shows a sketch of the ability to transfer electrons Fe2+ and Fe3+ due to oxidation and reduction processes [2] . Magnetite (Fe3O4) nanoparticles are used in several applications, such as nanofluid for heat transfer applications [3][4] , thermal conduktivity, density and adsorbent materials [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%